Awareness of Weight and Situation of Body Mass Index and Hypertension in Nepalese Teachers - Aryal, Bhagwan (Journal of Health Promotion, 2020)
Teachers are the role models to their students in terms of health and wellbeing, in particularly the nutritional status and physical outlook. These present opportunities to students for observational learning. However, many teachers face health complications which are not even perceived as a threat by them to their career and life. This study was conducted to determine the awareness of weight and current status of body mass index and hypertension among the Nepalese school teachers. It also examined the association between the BMI and hypertension. Randomly selected secondary level teachers in the Bagamati province of Nepal were the respondents. A cross-sectional descriptive research was conducted. Self-administered questionnaires were used to collect data. Age-wise relationship was found with BMI and hypertension. More the age, higher was the BMI category and so was the blood pressure. Risky situation of BMI and hypertension among senior teachers could create a threat to the teachers’ wellbeing and a setting for poor observational learning to the students. Teachers need to focus on improving their lifestyle and activities to better their conditions and present healthy role modeling.